Culture de sécurité et gestion du risque dans une entreprise de production de lait uruguayenne - Francisco Pucci; Soledad Nion (Revue Interventions Économiques)
This paper analyzes the risk management policies in the production largest dairy company of Uruguay. The security model of the company rests on rules and devices developed by security experts, but the normalization of deviation is a constant practice in the company, which undermines the effectiveness of the risk management policies implemented by management. While safety is an explicit value in the discourse of the organization, the underlying assumptions of organizational culture revolve around productivity and quality demands of production. This mismatch between explicit values and basic assumptions is expressed in the fact that the investment made by the company to buy personal protective equipment and Safety technological equipment is not accompanied by the concern to develop devices to force workers to use these facilities.